IN VIVO MAPPING OF CORTICAL COLUMNAR NETWORKS IN THE MONKEY WITH FOCAL ELECTRICAL AND OPTICAL STIMULATION - Anna Wang Roe (Frontiers in Neuroanatomy, 2015)
There are currently largescale efforts underway to understand the brain as connection machine. However, there has been little emphasis on understanding connection patterns between functionally specific cortical columns. Here, we review development and application of focal electrical and optical stimulation methods combined with optical imaging and fMRI mapping in the nonhuman primate. These new approaches, when applied systematically on a large scale, will elucidate functionally specific intra-areal and inter-areal network connection patterns. Such functionally specific network data can provide accurate views of brain network topology.